2016
DOI: 10.4103/2249-4863.197310
|View full text |Cite
|
Sign up to set email alerts
|

Health worker posting and transfer at primary level in Tamil Nadu: Governance of a complex health system function

Abstract: Background:Posting and transfer (PT) of health personnel – placing the right health workers in the right place at the right time – is a core function of any large-scale health service. In the context of government health services, this may be seen as a simple process of bureaucratic governance and implementation of the rule of law. However the literature from India and comparable low and middle-income country health systems suggests that in reality PT is a contested domain, driven by varied expressions of priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Local governance was a social accountability approach to enhance transparency and accountability at the local level. In three studies ( Cleary et al , 2013 ; Garimella and Sheikh, 2016 ; Panda et al , 2016 ), it was found to be effective by enabling space for decision-making at the local level. It improved health units’ performance by enhancing local authorities’ decision-making and enabling them to apply a bottom-up approach.…”
Section: Resultsmentioning
confidence: 99%
“…Local governance was a social accountability approach to enhance transparency and accountability at the local level. In three studies ( Cleary et al , 2013 ; Garimella and Sheikh, 2016 ; Panda et al , 2016 ), it was found to be effective by enabling space for decision-making at the local level. It improved health units’ performance by enhancing local authorities’ decision-making and enabling them to apply a bottom-up approach.…”
Section: Resultsmentioning
confidence: 99%
“…Due to power dynamics, the administrators are likely to prevail, leaving health workers with unmet needs [7]. The unmet needs facilitate dissatisfaction among health workers, which negatively affects health service delivery, for example by increasing absenteeism [24, 7, 25, 29].…”
Section: Discussionmentioning
confidence: 99%
“…In low- and middle-income countries (LMICs), posting and transfer (PT) practices, referring to how frontline health workers and administrators are geographically posted and transferred within public health facilities, have been recognized as a main barrier for having an effective workforce [13]. Previous studies found that health workers’ dissatisfaction with their postings and inadequate support for them to discharge their roles effectively are linked to absenteeism, low morale, and poor quality of health services [46].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations